2009
DOI: 10.1097/ogx.0b013e3181b2f273
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Perimenopause

Abstract: After completion of this article, the reader will be able to describe the types of female sexual disorders, summarize a plan of treatment for the different female sexual disorders, and outline special conditions during the perimenopause which might affect sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Seok et al reported a haemodynamic response of the pallidum and putamen during an event‐related functional MRI, and confirmed that these two regions were related to the physiology of sexual behaviour and reward‐related aspects of sexuality. A study by Novi et al confirmed that perimenopause presented a unique changes in sexual function and that perimenopausal women suffered from sex hormonal fluctuation‐induced decline in sexual function and desire. Therefore, the grey matter volume reduction of these two areas may affect sexual function and sexual desire for perimenopausal women.…”
Section: Discussionmentioning
confidence: 95%
“…Seok et al reported a haemodynamic response of the pallidum and putamen during an event‐related functional MRI, and confirmed that these two regions were related to the physiology of sexual behaviour and reward‐related aspects of sexuality. A study by Novi et al confirmed that perimenopause presented a unique changes in sexual function and that perimenopausal women suffered from sex hormonal fluctuation‐induced decline in sexual function and desire. Therefore, the grey matter volume reduction of these two areas may affect sexual function and sexual desire for perimenopausal women.…”
Section: Discussionmentioning
confidence: 95%
“…2 Furthermore, female sexual dysfunction (FSD) is believed to affect over 50% of women. 3 Female sexual dysfunction is a loss of desire for sexual activity that, in turn, causes significant distress and possible strain on interpersonal relationships. Diminished sexual arousal, dyspareunia, and difficulty achieving orgasm are also characteristics of FSD.…”
Section: Clinical Guidelines and Recommendations Conclusionmentioning
confidence: 99%
“…Low libido has been a complaint routinely voiced by menopausal women, and current reports cite that 16 million women older than 50 years experience low sexual desire . Furthermore, female sexual dysfunction (FSD) is believed to affect over 50% of women . Female sexual dysfunction is a loss of desire for sexual activity that, in turn, causes significant distress and possible strain on interpersonal relationships.…”
mentioning
confidence: 99%
“…S exual dysfunction is a common problem as women age and is a serious concern for perimenopausal women. [1][2][3][4] A survey of perimenopausal women in Europe found that 79% of participants agreed that it was very important to have a satisfying sex life. 5 One primary reason for increased reporting of sexual dysfunction during menopause is the decrease in estrogen levels during the menopausal transition as deficiencies in estrogen can lead to dry and painful sex.…”
Section: Introductionmentioning
confidence: 99%
“…5 One primary reason for increased reporting of sexual dysfunction during menopause is the decrease in estrogen levels during the menopausal transition as deficiencies in estrogen can lead to dry and painful sex. 1 However, other factors also play a role as sexual function is known to be multifactorial and complex. 1,6 Most studies examining sexual activity in menopausal women have been cross sectional 4,5,[7][8][9][10][11][12][13] and have been unable to capture the dynamics of changes during the meno-pausal transition.…”
Section: Introductionmentioning
confidence: 99%